PREVALENCE OF SUB CLINICAL MASTITIS IN DAIRY BUFFALOES OF PUNJAB, PAKISTAN - M. A. Ali; M. D. Ahmad; K. Muhammad; A. A. Anjum (Journal of Animal and Plant Sciences, 2011)
Six hundred lactating dairy buffaloes from four districts (Lahore, Sialkot, Narowal and Okara) of Punjab, Pakistan were screened for subclinical mastitis using White Side Test and subsequent bacterial isolation. Overall prevalence of subclinical mastitis was 44% (264/600). It was the highest (58%) in animals kept as individual holding at backyards followed by small holdings in periurban area (42%) and the lowest at organized farms with reasonable good managemental conditions (32%). Two hundred thirty four bacterial isolates of nine genera i.e. Staphylococci, Escherichia, Streptococci, Pseudomonas, Salmonellae, Bacillus, Klebsiella, Enterococci and Corynebacterium species were identified. The highest prevalence was of Staphylococci (28.32%) followed by Escherichia coli (16.18%), Pseudomonas (13.29%), Bacillus (12.42%), Streptococci (7.51%), Salmonellae (7.22%), Corynebacterium (6.64%), Klebsiella (5.20%) and Enterococci (3.17%).
Keywords: Buffaloes; Subclinical Mastitis; White Side Test; Prevalence; Pakistan.